"Bottom-up" self-assembly and "cold crystallization" of butterfly shaped tetrabenzofluorene molecules. Issue 31 (23rd May 2016) - Sampath, Srinivasan; Boopathi, A. A.; Mandal, A. B.
Abstract : We report the unprecedented "cold crystallization" in polycyclic aromatic molecules and a unique "bottom-up" self-assembly process in butterfly-shaped molecules. Abstract : Butterfly-shaped tetrabenzo[ a, c, g, i ]fluorene (TBF)-based molecules (1 and2 ) were designed, synthesized and well characterized using various spectroscopic techniques. The single crystal X-ray structure of1 shows the presence of intermolecular 3-D π–π stacking interaction and unprecedented "cold crystallization" in polycyclic aromatic molecules. We report for the first time, the "bottom-up" self-assembly of TBF based organic molecules. The supramolecular studies reveal the formation of vesicles and cuboid-shaped nanocrystals in THF–water and toluene solution, respectively.